Antibacterial Efficacy of Solid-State Cu²⁺ Exchanged Clinoptilolite: Structural Characterization and Microbial Resistance - Sajad Faryad; Mohammad Ghorbanpour (Journal of Water and Environmental Nanotechnology)
Cu2+ exchanged clinoptilolites were synthesized through a straightforward and economical solid-state cation exchange technique. The antibacterial efficacy of these solid-state Cu2+-exchanged clinoptilolites was assessed utilizing the disc diffusion method. The microstructural characteristics of the exchanged clinoptilolites were examined to determine their microstructural properties using X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), and Brunauer-Emmett-Teller (BET) techniques. The results revealed slight modifications in the crystalline structure of clinoptilolite, along with the detection of both Cu2+ ions and copper oxide after the ion exchange process. During this process, the BET surface area exhibited a reduction from 31.1 m²/g to 28.2 m²/g. Furthermore, the SEM analysis revealed that the ion exchange process preserved the original morphology of clinoptilolite, exhibiting only minor alterations. The EDX analysis corroborated the effective substitution of cations within the clinoptilolite framework with copper ions. UV-visible spectroscopy indicated the presence of both Cu2+ ions and the copper oxide form in the exchanged samples. The prepared samples displayed antimicrobial properties against Escherichia coli and Staphylococcus aureus bacteria. Notably, the Cu2+ exchanged clinoptilolite exhibited superior antibacterial activity against S. aureus compared to E. coli. These findings suggest that Solid-state Cu2+ exchanged clinoptilolite has the potential as an effective antibacterial agent for purifying water contaminated with bacteria.